Blockade of IGF2R improves muscle regeneration and ameliorates Duchenne muscular dystrophy. Issue 1 (2nd December 2019) - Bella, Pamela; Farini, Andrea; Banfi, Stefania; Parolini, Daniele; Tonna, Noemi; Meregalli, Mirella; Belicchi, Marzia; Erratico, Silvia; D'Ursi, Pasqualina; Bianco, Fabio; Legato, Mariella; Ruocco, Chiara; et al.
Abstract: Duchenne muscular dystrophy (DMD) is a debilitating fatal X‐linked muscle disorder. Recent findings indicate that IGFs play a central role in skeletal muscle regeneration and development. Among IGFs, insulinlike growth factor 2 (IGF2) is a key regulator of cell growth, survival, migration and differentiation. The type 2 IGF receptor (IGF2R) modulates circulating and tissue levels of IGF2 by targeting it to lysosomes for degradation. We found that IGF2R and the store‐operated Ca 2+ channel CD20 share a common hydrophobic binding motif that stabilizes their association. Silencing CD20 decreased myoblast differentiation, whereas blockade of IGF2R increased proliferation and differentiation in myoblasts via the calmodulin/calcineurin/NFAT pathway. Remarkably, anti‐IGF2R induced CD20 phosphorylation, leading to the activation of sarcoplasmic/endoplasmic reticulum Ca 2+ ‐ATPase (SERCA) and removal of intracellular Ca 2+ . Interestingly, we found that IGF2R expression was increased in dystrophic skeletal muscle of human DMD patients and mdx mice. Blockade of IGF2R by neutralizing antibodies stimulated muscle regeneration, induced force recovery and normalized capillary architecture in dystrophic mdx mice representing an encouraging starting point for the development of new biological therapies for DMD. Synopsis: IGF2R is over‐expressed in Duchenne Muscular Dystrophy (DMD) and mdx muscles. Blockade of IGF2R rescued the dystrophic muscle phenotype, ameliorated vascular architecture defects and improved muscle force. IGF2R expression is increased in dystrophic muscles and binds to CD20. Blockade of IGF2R facilitates IGF2‐IGF1R interactions and activates CD20 phosphorylation, promoting the entrance of Ca 2+ ions in the sarcoplasm. Increasing levels of Ca 2+ ions regulate calcineurin/CaMKII pathway and activates SERCA1 leading to in vitro premature myogenic differentiation and in vivo increased force production and vasculature remodeling. Blockade of IGF2R reestablished the correct oscillating pattern of Ca 2+ ion levels in the microenvironment of myofibrils and protects from muscular dystrophy acting on different mechanisms of dystrophic muscles. Despite this variety of mechanisms of action, monoclonal antibodies can be used in DMD to normalize the over‐expression of IGF2R and the availability of muscle IGFs. Abstract : IGF2R is over‐expressed in Duchenne Muscular Dystrophy (DMD) and mdx muscles. Blockade of IGF2R rescued the dystrophic muscle phenotype, ameliorated vascular architecture defects and improved muscle force.